Short-range order in bulk Zr- and Hf-based amorphous alloys - Damonte, Laura Cristina (2000)
The local order in mechanically alloyed Hf65Al7.5Cu17.5Ni10 and Zr65Al7.5Cu17.5Ni10 amorphous alloys was studied by means of perturbed angular correlation measurements. The amorphous state of the starting material was confirmed by X-ray diffraction. Differential scanning calorimetry analysis showed the existence of an extended supercooled liquid region. Two exothermic effects, indicating a two-step crystallization process, were also observed. Perturbed angular correlation measurements indicated similar short-range order in the supercooled liquid state and in the starting amorphous state. The evolution of short-range order with annealing temperature was also studied ,being the intermediate and final phases characterized by this hyperfine technique. perturbed angular correlation measurements. The amorphous state of the starting material was confirmed by X-ray diffraction. Differential scanning calorimetry analysis showed the existence of an extended supercooled liquid region. Two exothermic effects, indicating a two-step crystallization process, were also observed. Perturbed angular correlation measurements indicated similar short-range order in the supercooled liquid state and in the starting amorphous state. The evolution of short-range order with annealing temperature was also studied ,being the intermediate and final phases characterized by this hyperfine technique. 65Al7.5Cu17.5Ni10 and Zr65Al7.5Cu17.5Ni10 amorphous alloys was studied by means of perturbed angular correlation measurements. The amorphous state of the starting material was confirmed by X-ray diffraction. Differential scanning calorimetry analysis showed the existence of an extended supercooled liquid region. Two exothermic effects, indicating a two-step crystallization process, were also observed. Perturbed angular correlation measurements indicated similar short-range order in the supercooled liquid state and in the starting amorphous state. The evolution of short-range order with annealing temperature was also studied ,being the intermediate and final phases characterized by this hyperfine technique.